SUN CITY - Pedersen, Max (Tidsskriftet Antropologi, 2003)
Geographically Sun City is a town of 40.000 people. It is located in the desert 12 miles north of Phoenix in Arizona. The winters are dry and mild. The summers are hot as hell. And the sunsets are always spectacular. Historically Sun City was founded in 1960 by a local tycoon who owned The New York Yankees through the Fifties. The town is the first active adult community in the US and the mother of all similar communities that have spread out through the country during the last 44 years. Sociologically Sun City is a mixture of a middle class suburb, a gerontological ghetto, a classical American utopian community and a social laboratory in which the inhabitants have been experimenting with new ways of senior living. And finally Sun City and other retirement communities are often seen as being either a good or bad way of living in old age. This way of looking at things has not done much good to the understanding of Sun City.